Waiting for "God's Best": Love and Sex in Evangelical Christianity in the Philippines - Cornelio, Jayeel (Journal of religion and popular culture, 2022)
Echoing the writings of their American counterparts, Filipino evangelicals have published bestselling books on love and sex. These books appeal because of their practical tips, often narrated in conversational Tagalog and English. We turn to some of the most influential books in this article. These works exhort their readers to embrace sexual purity in preparation for the one God intends for them—"God's best." Although decidedly evangelical, these writings are packaged within the language of a secular genre—love and relationships—known for espousing more liberal views on romance and sexuality. Two rhetorical techniques matter: (1) the simultaneous promotion and disavowal of courtship; and (2) the use of religious testimony. The article ends with critical reflections on evangelicalism as a countercultural movement in Philippine society.